Julius Caesar : Lessons in Leadership From the Great Conqueror - Yenne, Bill, 1949- (New York Palgrave Macmillan, 2012)
No ancient ruler inspired more legends than Julius Caesar. Under his leadership, Rome conquered territory throughout Europe and the Mediterranean. In this fast-paced look at one of the world's greatest generals, acclaimed author Bill Yenne charts the major events that shapedhis leadership,his rise to power, and his crashing fall
Include Note and Index
Keywords: Political leadership -- Military leadership -- Rome (Empire)